LINGUVOCOGNITIVE STUDY OF THE CONCEPT OF TOLERANCE IN RELIGIOUS TEXTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article approaches the concept of tolerance in religious texts on the basis of cognitive linguistics. It is revealed that the text is the central core in the semanticsyntactic structure. It has been shown that explicit and implicit meanings can be expressed in the text and embodied pragmatic meanings in the text.